From Antz to Titanic : reinventing film analysis - Barker, Martin, 1946-; Austin, Thomas, 1966- (London ; Sterling, VA : Pluto Press, 2000)
Rejecting much of the baggage that surrounds contemporary film analysis, the authors work back from the problems their students have encountered to literally strip the subject of film analysis down to its bare essentials.
Films, audiences and analyses -- Formalism and the implied audience -- Usual suspects, unusual devices -- 'An ant with ideas ... ' -- Titanic : a knight to remember -- In the jungle, the mighty jungle -- 'Like food processors, but nasty' -- Dear Meg, dearest Tom -- A very deep impact / with Thomas Austin -- Showing that it is what it is.
Includes bibliographical references (pages 211-215); filmography (pages 216-218) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Film criticism; Critique cinématographique.; PERFORMING ARTS -- Film & Video -- History & Criticism; SOCIAL SCIENCE -- Anthropology -- Cultural; Film criticism; Filmkritik; Filmanalyse; Filmtheorie